Becoming an Anti-Racist Music Educator: Resisting Whiteness in Music Education. (June 2021) - Hess, Juliet
In this article, I propose some ways that music educators might become anti-racist. I explore the ways that Whiteness manifests in music education and subsequently examine actions we might take to resist this Whiteness. Ultimately, I suggest anti-racism as a way forward for music education. I delineate some of the ways that Whiteness operates in music education, not to discourage educators but rather to encourage us to notice the way Whiteness pervades our field.